Дослідження та аналіз факторів середовища підприємства - Багорка, Марія Олександрівна; Bahorka, Mariia; Кадирус, Ірина Григорівна; Kadyrus, Iryna; Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Науково-освітній інноваційний центр суспільних трансформацій м. Чернігів, 2022)
В статті представлені результати PEST і SWOT- аналізу основних факторів зовнішнього і внутрішнього середовища ТОВ «РУШ». За результатами PEST-аналізу встановлено, що для ТОВ «РУШ» з боку зовнішнього оточення обґрунтована перевага сильних позицій над слабкими. Представлений вид аналітичного дослідження дозволив зробити висновки щодо впливу з боку політики, економіки, зміни у технологіях та соціальних нормах на систему продажу продукції базового підприємства. При проведенні SWOT-аналізу до уваги приймали показники чотирьох сфер роботи підприємства. В результаті аналізу за моделлю SWOT, що виконано для базового підприємства, розроблено певні стратегії подальших маркетингових дій та управління підприємством. Сформульовано чотири види стратегій, за результатами яких можливо пропонувати товариству конкретні заходи щодо вдосконалення процесів. Для оцінювання конкурентної спроможності ТОВ «РУШ» з її основним конкурентом «Prostor» проведена оцінка основних компонентів, які визначають рівень конкурентної спроможності кожного з підприємств. The article presents the results of PEST and SWOT analysis of the main factors of the external and internal environment of enterprise «RUSH». The opportunities and problems that arise and can affect the enterprise also indicate the promising growth of the company, because the opportunities are more than the threats. It should be noted that the enterprise under investigation can occupy new segments on the market due to the expansion of product assortment groups, strengthening of business reputation and the use of new technologies in the field of sales. Based on the results of the PEST analysis, it was established that the advantage of strong positions over weak ones is justified for enterprise «RUSH» from the external environment. The presented type of analytical research made it possible to draw conclusions about the influence of politics, economics, changes in technology and social norms on the system of selling products of the base enterprise. When conducting a SWOT analysis, indicators of four areas of the enterprise’s work were taken into account. As a result of the SWOT model analysis performed for the base enterprise, certain strategies for further marketing actions and enterprise management were developed. Four types of strategies have been formulated, based on the results of which it is possible to offer the company specific measures to improve processes. Summarizing the SWOT model for the company and marketing research management, it was established that due to strong positions, it is possible to counter threats on the market and through improvements in pricing policy, motivational management, and personnel management, it is possible to achieve competitive advantages. In order to assess the competitiveness of enterprise «RUSH» with its main competitor Prostor, an assessment of the main components that determine the level of competitiveness of each of the enterprises was carried out. In the conditions of the changing and dynamic marketing environment in which the company under study currently operates, marketing research will provide an opportunity to determine the areas of effective functioning in the conditions of competition, search for reserves to increase its competitiveness and choose effective areas for further development.
Research and analysis of enterprise environmental factors
Keywords: маркетингові дослідження; marketing research; PEST та SWOT- аналіз; PEST and SWOT analysis; фактори середовища; environmental factors; маркетингова стратегія; marketing strategy; управління маркетингом; marketing management